Relevance of the Book of Tafsir Ahkamul Qur'an by Ibn Al-‘Arabi to the book of Fiqh Al-Mughni by Ibn Qudamah (Case Study of Q.S. Al-Baqarah verse 229) - Anis Kusumawardani; Kharis Nugroho; Abdullah Mahmud; Mutohharun Jinan; Andri Nirwana AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to find the relevance between tafsir and fiqh products from different schools of thought but written in close periods, namely the book of interpretation of the Ahkamul Qur'an by Ibn 'Arabi of the Maliki school of thought and the book of al-Mughni fiqh by Ibnu Qudamah of the Hambali school of thought so that a point can be found similarities and differences between the two. This research is qualitative in nature with library data and primary sources in Q.S. al-Baqarah [2]: 229 which discusses talaq. This research is literature research on the methodology of writing books written by these two figures. Comparative studies are carried out to reveal the similarities and differences between the two in order to find the relevance of each other. Researchers revealed that the two figures had different lines of thought. However, Ibn 'Arabi's Ahkamul Qur'an is proven to have relevance to the writing process of Ibn Qudamah's book al-Mughni.